Synergistic effect of talc/carbon spheres composite as oil‐based additive enhancing the lubricating properties for steel‐steel contact. (7th January 2020) - Fei, Jie; Qi, Ying; Luo, Lan; Gu, Yuefeng; Huang, Jianfeng
Abstract: Talc/carbon spheres (TC) composite was successfully fabricated through a simple and eco‐friendly hydrothermal method. The tribology properties of the base oil were significantly improved after adding TC composites, which had been studied by a ball on disc (BOD) tribometer. The friction coefficient of oil containing 0.5‐wt% TC composite (0.5 TC‐Oil) was only 0.08, with a decrease of 35.3% compared with the base oil at 5 N. Moreover, severe abrasive wear between friction pairs changed into slight plastic deformation lubricated with 0.5 TC‐Oil, as confirmed by scanning electron microscope (SEM). These results reflected notable synergy between self‐repair performance effect of talc and ball‐bearing effect of carbon spheres. The study displayed the potential lubricating performance of the TC composite in current generation oil lubricants.